1984
DOI: 10.1111/j.1432-1033.1984.tb08282.x
|View full text |Cite
|
Sign up to set email alerts
|

Topological aspects of microsomal N‐acetyltransferase, an enzyme responsible for the acetylation of cysteine S‐conjugates of xenobiotics

Abstract: Acetylation of cysteine S-conjugates of xenobiotics by microsomal N-acetyltransferase is the final step of detoxicative metabolism leading to mercapturic acid biosynthesis. To elucidate the subcellular site of N-acetylation and the effective mechanism by which the final metabolites are eliminated from the organisms, topological aspects and catalytic properties of microsomal N-acetyltransferase and mercapturic acid biosynthesis in vivo were investigated. Intravenous administration of radioactive S-benzyl-L-cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…However, the determinants of its association with the ER and the orientation of its catalytic site (cytosolic or luminal) remain unknown. The related human enzyme, NAT8 (N-acetyltransferase 8), which shares approximately 30 % sequence identity with NAT8L and is expressed in kidneys and liver, was shown to catalyse the acetylation of cysteine-S-conjugates and to be also associated with the ER [11], consistent with the previous subcellular localization of this enzymatic activity [12]. No consensus has yet been reached on the subcellular localization of NAT8L, as Ariyannur et al [8] reported a partial mitochondrial localization of the endogenous protein in SH-SY5Y cells, using antibodies directed against NAT8L peptides.…”
Section: Introductionsupporting
confidence: 82%
“…However, the determinants of its association with the ER and the orientation of its catalytic site (cytosolic or luminal) remain unknown. The related human enzyme, NAT8 (N-acetyltransferase 8), which shares approximately 30 % sequence identity with NAT8L and is expressed in kidneys and liver, was shown to catalyse the acetylation of cysteine-S-conjugates and to be also associated with the ER [11], consistent with the previous subcellular localization of this enzymatic activity [12]. No consensus has yet been reached on the subcellular localization of NAT8L, as Ariyannur et al [8] reported a partial mitochondrial localization of the endogenous protein in SH-SY5Y cells, using antibodies directed against NAT8L peptides.…”
Section: Introductionsupporting
confidence: 82%
“…However, albuminligand interaction may become critically important if the rates of formation of such hazardous metabolites were increased, such as for bilirubin in acute hemolysis, or if animals were challenged with high doses of electrophilic xenobiotics, which would be metabolized to the corresponding mercapturic acids. Recent studies [20] revealed that the N-acetylation of a cysteine S-conjugate is catalyzed by the transferase at the cytoplasmic surface of endoplasmic reticulum in liver and kidney and that cytosolic organic anion-binding proteins (ligandins) facilitate this reaction by binding the N-acetylated reaction products and other competing organic anions. Thus, in addition to the interaction with cytosolic ligandins, binding to the circulating albumin may constitute an important step in the interorgan metabolism and transport leading to mercapturic acid biosynthesis and a final elimination of metabolites from the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on microsomal preparations have shown that the active site of CCNAT is localized to the cytoplasmic side of the endoplasmic reticulum (ER) (Elce, 1970;Green and Elce, 1975;Okajima et al, 1984). The CCNAT co-substrate acetyl-CoA is localized in the cytosol at high concentrations to facilitate rapid and efficient N-acetylation of Cys conjugates (Garland et al, 1965).…”
Section: Cysteine S-conjugate N-acetyltransferasementioning
confidence: 99%